Dando voz aos estudantes na cidade de Goiânia/GO: investigações sobre a “crise” entre os jovens e o ensino médio - Bungenstab, Gabriel Carvalho (2016)
This thesis aims to contribute to the debate about youth and high school, specifically trying to understand and analyze whether we are experiencing a crisis in youth relationship with high school or if there is no crisis. He started from the hypothesis that within the school there are different youths and, because of this, young people will relate in different ways to this institution. This means that, according to each youth idea that students have, they can weave relationships more resistance before school or may be more likely to adapt to school reality of high school. To this end, the survey was conducted with young people in high school in the city of Goiânia, Goiás Capital. For this, the thesis is organized in five chapters. The first is devoted to the methodological work route explanation. At that time, justify the choice to apply a questionnaire with young students from four high schools in city of Goiânia. The second chapter is devoted to theoretical, discussion about the sociological concept of youth in modern society (and contemporary) from the lens of European and Brazilian authors. The third aimed to understand who the 297 surveyed youths. Already four chapter analyze the data collected in the field in order to clarify issues relating to young students and their schools. These analyzes indicate that students have diverse views about their schools. It is from these views that they will position themselves about the possible crisis involving high school. Finally, it concludes the urgent need to understand who are the young people attending the public high school because it is through this understanding that comes to understanding the crisis has partially.